Cocaine-Seeking Behavior Induced by Orexin A Administration in the Posterior Paraventricular Nucleus of the Thalamus Is Not Long-Lasting: Neuroadaptation of the Orexin System During Cocaine Abstinence - Matzeu, Alessandra; Martin-Fardon, Rémi (Frontiers in Behavioral Neuroscience, 2021)
Hypothalamic orexin (Orx) projections to the paraventricular nucleus of the thalamus (PVT) have received growing interest because of their role in drug-seeking behavior. Using an established model of cocaine dependence (i.e., long access [LgA] to cocaine), we previously showed that OrxA injections in the posterior PVT (pPVT) reinstated extinguished cocaine-seeking behavior in rats after an intermediate period of abstinence (2-3 weeks). Considering the long-lasting nature of drug-seeking behavior, the present study examined whether the priming effect of intra-pPVT OrxA administration was preserved after a period of protracted abstinence (4-5 weeks) in rats that self-administered cocaine under LgA conditions. Furthermore, to better understand whether a history of cocaine dependence affects the Orx system—particularly the hypothalamic OrxpPVT connection—the number of Orx-expressing cells in the lateral hypothalamus (LH), dorsomedial hypothalamus (DMH), and perifornical area (PFA) and number of orexin receptor 1 (OrxR1)- and OrxR2-expressing cells in the pPVT were quantified. Orexin A administration in the pPVT induced cocaine-seeking behavior after intermediate abstinence, as reported previously. At protracted abstinence, however, the priming effect of OrxA was absent. A higher number of cells that expressed Orx was observed in the LH/DMH/PFA at both intermediate and protracted abstinence. In the pPVT, the number of OrxR2-expressing cells was significantly higher only at intermediate abstinence, with no changes in the number of OrxR1-expressing cells. These data build on our previous findings that the hypothalamic OrxpPVT connection is strongly recruited shortly after cocaine abstinence and demonstrate that the priming effect of OrxA is not long lasting. Furthermore, these findings suggest that throughout abstinence, the OrxpPVT connection undergoes neuroadaptive changes, reflected by alterations of the number of OrxR2-expressing cells in the pPVT.